ANÁLISIS Y EVALUACIÓN ECONÓMICA Y FINANCIERA A LA EMPRESA “ELECTROCOMPU”, DE LA CIUDAD DE LOJA, PERIODO 2013-2014 - Valle Pineda, Diana Carolina (2016)
The thesis entitled: ANALYSIS AND EVALUATION ECONOMIC AND FINANCIAL COMPANY “ELECTROCOMPU " LOJA CITY , PERIOD 2013-2014 , the same as was done to meet the pre- opt the title of Engineer in Accounting requirement and audit , Public Auditor - Accountant. For proper process was necessary to take into account compliance with each of the objectives, being the general analysis and economic and financial evaluation which was necessary to analyze the economic activity of the company, it allowed its position , performance and profitability in the years 2013-2014 . The thesis presents a theoretical part corresponding to the theoretical foundations of analysis and economic and financial assessment recommends financial analysis, allowing to evaluate the position of the company in different aspects by vertical and horizontal analysis of financial statements and application of indicators to measure the economic and financial performance as Eva , Dupont Breakeven System and then report the results to the owner of the company so you can take appropriate corrective action. After fulfilling the objectives set by the financial analysis it was determined that the company “ELECTROCOMPU” is a company that has a good financial situation, with good assets, solid assets and liabilities moderate distribution. It also maintains sufficient liquidity, adequate product portfolio turnover, inventory and